Tattoos as Narratives: Skin and Self - Martin, Chris William (Public Journal of Semiotics, 2013)
This article explores the polysemic nature of contemporary tattoos by comparing interviewees‘ perceptions of the meanings of their tattoos with the meanings which can be imputed to them by a researcher studying cultural history and semiotics. After systematically comparing the referencing and mapping of tattoos by interviewees in St. John‘s, Newfoundland, the author argues that tattoos should be viewed in a light that reflects the endless potential of human self-expression. Part of this statement is meant to address the structure-agency dichotomy which has long been reflected in the literature on sociological theories and the tattooing/body literature. Another part is meant to give substantive evidence to the claim that regardless of motivations or meanings, the truth behind meaning and identity can only be found in complex and ephemeral moments which populate the life of the cultural and individual actor.